Pengaruh Citra Merek, Kualitas Produk Dan Word Of Mouth (WOM) Terhadap Keputusan Pembelian Konsumen Motor Honda Berangka Esaf - Rozi, A; Budianto, Achyat; Evrina, Evrina; Marnas, Marnas; Fadillah, Akbar (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
Currently, there is lively discussion surrounding the enhanced Smart Architecture Frame (ESAF) used in Honda motorcycles. The ESAF frame has drawn attention due to claims that it easily rusts, becomes brittle, and breaks. Several videos showing corroded, fragile, and fractured ESAF frames have gone viral on social media. The objective of this research is to examine the relationship between Brand Image, Product Quality, and Word of Mouth (WOM) on the purchasing decisions of Honda motorcycles equipped with ESAF in Karawang. The study employs a quantitative approach with a causal-comparative research design, which investigates cause-and-effect relationships between two or more variables. The research population consists of Honda motorcycle club members in Karawang, and the sampling method used is judgmental sampling. A total of 50 respondents participated in the study. Data collection was conducted through questionnaire surveys. The research findings indicate that Brand image has a positive influence, but it is not statistically significant regarding purchasing decisions for Honda motorcycles equipped with ESAF in Karawang. The significance value is 0.263, indicating that the brand image variable does not significantly impact because its value is above 0.05. Product quality has a positive and significant influence on purchasing decisions for Honda motorcycles equipped with ESAF in Karawang. Word of Mouth (WOM) has a positive and significant influence on purchasing decisions for Honda motorcycles equipped with ESAF in Karawang